Corporate social responsibility level - theoretical approach = Poziom społecznej odpowiedzialności przedsiębiorstw - ujęcie teoretyczne - Rojek-Nowosielska, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The paper presents a theoretical method for assessing the level of corporate social responsibility (CSR) using original concept of CSR continuum model (CSR CM). The CSR CM constitutes from two main parameters: the institutional level of CSR and the CSR area. Theoretical background for the institutional levels is the CMM concept. The identified areas of the CSR CM consist of such as: employees, customers, suppliers, local community and natural environment.
Keywords: społeczna odpowiedzialność przedsiębiorstw (SOP); Model Dojrzałości Procesowej CMM; poziom SOP; model kontinuum; Corporate Social Responsibility (CSR); Capability Maturity Model (CMM); level of CSR; continuum model